Solving Schrödinger Wave Equation for the Charmonium Spectrum Using Artificial Neural Networks - Tariq Mahmood; Jumanah Ahmed Darwish; Talab Hussain; Maqsood Ahmed; Rehan Ahmad Khan Sherwani (Advances in High Energy Physics)
In this study, we solved the Schrödinger wave equation by using effective potential in an artificial neural network (ANN) for the mass spectrum of different charmonium states, including ηc, ψ2, χ2, and  χ4. The ANN approach provides an efficient, more general, and continuous solution-approximating strategy, thus eliminating the possibility of skipping any region of interest in mass spectroscopy. The close consistency of ANN results with the already-reported results from numerical and theoretical approaches and experimental ones shows the reliability and accuracy of the ANN approach.